GENEALOGI FILSAFAT ISYRA>Q DAN STRUKTUR PENGETAHUANNYA - Mohamad Anas (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
The discourse of epistemological conflict in the Islamic thought is still prevailing in this multicultural era. The emergence of inter-religious problem is one of a clear example that emanate from epistemological debate. This problem is expected to end through collaboration between the two, or at least epistemological dialogue. In the history of Islamic thought, there was a great debate between knowledge systems hud}u>ri> which was the continuation of ancient pre-islamic tradition (al-mauru>s\ al-qadi>m)- and knowledge of knowledge syar’i> (baya>ni). Ultimately, by integrating between hud}u>ri> and syar’i> or between z}a>hir and ba>t}in, the discourse is ended. Suhrawardi has combined between knowledge of hud}u>ri> with rational knowledge. Ultimately, through exhausting effort he was able to generate knowledge system which is known as the philosophy of isyra>q